2006
DOI: 10.1089/ten.2007.13.ft-314
|View full text |Cite
|
Sign up to set email alerts
|

The Cytocompatibility and Early Osteogenic Characteristics of an Injectable Calcium Phosphate Cement

Abstract: In this study, the cytocompatibility and early osteogenic characteristics of rat bone marrow cells (RBMCs) on injectable calcium phosphate (CaP) cement (Calcibon) were investigated. In addition to unmodified CaP cement discs, 2 other treatments were given to the discs: preincubation in MilliQ and sintering at different temperatures. After primary culture, RBMCs were dropwise seeded on the discs and cultured for 12 days. The samples were evaluated in terms of cell viability, morphology (live and dead assays and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 42 publications
0
16
1
Order By: Relevance
“…For example, the data on cytocompatibility and early osteogenic characteristics are available in literature [475]. The ratio of the cases determined to be "effective" or "better" among the 74 cases we found to be 97.3 % [476].…”
Section: Clinical and Medical Applicationsmentioning
confidence: 75%
“…For example, the data on cytocompatibility and early osteogenic characteristics are available in literature [475]. The ratio of the cases determined to be "effective" or "better" among the 74 cases we found to be 97.3 % [476].…”
Section: Clinical and Medical Applicationsmentioning
confidence: 75%
“…Previous studies showed that human stem cell attachment to CPC was relatively poor. 40,41 The tripeptide RGD sequence can promote the attachment of cells because it is recognized by the adhesion receptors on the cell membrane. Thus, the affinity between cells and biomaterials could be improved by the immobilization of RGD, which can mimic the natural extracellular matrix.…”
Section: Resultsmentioning
confidence: 99%
“…However, previous studies showed that human stem cell attachment to CPC was relatively poor. 40,41 Therefore, there is a need to improve the cell attachment to CPC. Two hypotheses were tested: (1) hESC-derived MSCs can successfully undergo osteogenic differentiation on the CPC-chitosan scaffold; (2) RGD incorporation will greatly enhance hESC-derived MSC attachment, osteogenic differentiation, and synthesis of bone minerals on the CPC-chitosan scaffold.…”
mentioning
confidence: 99%
“…For example, the data on cytocompatibility and early osteogenic characteristics are available in literature [543]. The ratio of the cases determined to be -effective‖ or -better‖ among the 74 cases we found to be 97.3% [544].…”
Section: Biomedical and Clinical Applicationsmentioning
confidence: 74%